Simple tools and techniques of enterprise risk management - Chapman, Robert J. (Chichester, West Sussex, England ; Hoboken, NJ : J. Wiley & Sons, 2006)
This book clearly recognizes the importance of risk identificaion by describing the sources of risk, which are explored in detail.
Includes index.
aug 28/05/13
Loans
Keywords: Risk management; Risk; Uncertainty; Decision making